The Role of Risk Management in Improving Patient Safety at Budi Kemuliaan Hospital, Batam - Susanna Halim; Juanna Soehardy; Alamsyah (Jurnal Penelitian Pendidikan IPA, 2026)
The research investigates how risk management strategies contribute to enhanced patient safety in hospitals, with empirical evidence using data from a tertiary hospital in Indonesia. The study utilized a descriptive qualitative design supported by descriptive statistics. Primary data were collection involved in-depth interviews with four important informants, and qualitative secondary data were analysis included descriptive statistics, normality testing, and Spearman correlation analysis. Qualitative data were analyzed through thematic analysis and data triangulation. The study’s results indicate that despite high ratings for service quality and  patient satisfaction were rated very highly, no statistically significant correlation was identified between these variables (r = −0.003; p = 0.984). Qualitative data, however, suggests that patient safety is predominantly shaped by governance-based risk management systems, organizational safety culture, and strong leadership dedication. This research offer fresh empirical evidence that patient satisfaction cannot serve as a proxy indicator for patient safety. Instead, patient safety should be evaluated through systemic, preventive, and sustainable risk management frameworks. These results contribute to the theoretical discourse on healthcare quality management and offer practical implications for hospital leaders in strengthening patient safety governance in complex healthcare environments.